Mathematical activities and critical thinking ability in Lagosi weaving process of the Buginese community - Pathuddin, Hikmawati; Mariani, Andi; Busrah, Zulfiqar; Kamariah, Kamariah; Syukur, Syamzan (Journal of Honai Math, 2024)
Lagosi, a renowned woven fabric of national significance, involves a precise calculation formula in its manufacturing process. Craftsmen must meticulously count the threads to ensure the motif aligns with the intended design. Despite its importance, this aspect has not been thoroughly examined within the framework of Ethnomathematics. Consequently, this study investigates the mathematical practices employed by the Buginese people during the Lagosi weaving process, focusing on both the manufacturing procedures and the resultant motifs. Employing a qualitative methodology with an ethnographic approach, this research collected data through observation, interviews, and audio-visual documentation. The analysis utilized domain and taxonomic techniques to interpret the data. To ensure validity, both source and method triangulation were employed. The findings reveal that the crafting of Lagosi involves integrating counting, measuring, designing, and positioning techniques. Additionally, the study demonstrates that weaving artisans apply mathematical critical thinking skills in the production of Lagosi. The weaving process also reflects socio-cultural values such as diligence, perseverance, discipline, and faith. These insights contribute to a deeper understanding of mathematics in cultural contexts and offer valuable perspectives for contextual mathematics education by incorporating social values.